Manufacturing, services and premature deindustrialization in developing countries: A Kaldorian analysis - Sukti Dasgupta; Ajit Singh (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
This paper uses a Kaldorian framework to examine the evidence of deindustrialization in developing countries at low levels of income, the jobless growth in these economies and the fast expansion of the informal sector. The questions are specifically examined for the Indian economy, using state level data but the analysis has a wider application for economic policy in developing countries. – deindustrialization ; manufacturing ; services ; jobless growth ; developing countries
Keywords: O14; 330; Deindustrialisierung; Verarbeitendes Gewerbe; Entwicklungsländer; Indien